TOILET TRAINING THERAPY APPLICATION FOR CHILDREN WITH AUTISM BASED ON ANDROID - Sudiatmika, I Putu Gede Abdi; Dewi, Komang Hari Santhi (Universitas Pendidikan Ganesha, 2018)
Autis is one of psychic disorder psychological due to a nervous breakdown on child that will influence are sprouting children be assessed in terms of social, emotional about the nature of children. Today the trend of children people disorder autism spectrum the number was growth. Handling children autis adult was conducted in the centers autis and in some center autis other. Children autis grouped based on compliance. Children autis having compliance low given intervening or handling of the introduction of a toilet that better known for toilet training to provide understanding to to the toilet independently. But the cost of therapy or there has been significant intervention upon a center or center autis relative expensive and it comes tend to only 1 an hour and a half , despite the fact that this for a child with special needs disabled athletes need the time which long enough to comprehending a a particular command . Parents did not pay too expected will be able to perform the activities of these interventions in the house of . To the lack of knowledge on the part of parents points about how to give the introduction of the toilet to the child make on the part of parents accepted islam it is they had a limited impact on the state of the child .Â Pemaran may look on their stripped to the capital market and it is extremely necessary to an application that contains information or langkah-langkah to melaksanakn therapy in the house .Â This application is reasonable enough this one is evolved on a mobile device with a system of the operation of the android based